A Class of Integral Operators Preserving Subordination and Superordination for Analytic Functions. (16th August 2012) - Al-Kharsani, H. A.; Al-Areefi, N. M.; Sokół, Janusz
Abstract : The purpose of the paper is to investigate several subordination- and superordination-preserving properties of a class of integral operators, which are defined on the space of analytic functions in the open unit disk. The sandwich-type theorem for these integral operators is also presented. Moreover, we consider an application of the subordination and superordination theorem to the Gauss hypergeometric function.